The merchant of Venice - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
The Merchant of Venice is one of the most outstanding romantic comedies of William Shakespeare. The play revolves around the legendary characters of Antonio, a rich Italian merchant, Shylock, a rich Jew, and Portia, a rich heiress. When Antonio asks to borrow money from Shylock to help his friend Bassanio, Shylock agrees on the condition that if he is unable to repay it by the date specified, he will have to repay it with a pound of his flesh. As the play unfolds, Antonio is trapped by Shylock s condition, but the beautiful and intelligent Portia comes to his rescue. This short narrative version of the play has been suitably adapted to help introduce the play to young readers
Keywords: Adaptations Juvenile literature